1997
DOI: 10.1042/bj3210759
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic stimulation of lipoprotein lipase gene expression in rat brown adipocytes differentiated in culture: mediation via β3- and α1-adrenergic receptors

Abstract: In order to investigate whether the positive effect of adrenergic stimulation on lipoprotein lipase (LPL) gene expression in brown adipose tissue is a direct effect on the brown adipocytes themselves, the expression of the LPL gene was investigated by measuring LPL mRNA levels in brown adipocytes, isolated as precursors from the brown adipose tissue of rats and grown in culture in a fully defined medium before experimentation. Addition of noradrenaline led to an enhancement of LPL gene expression; the mRNA lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 64 publications
(89 reference statements)
1
9
0
Order By: Relevance
“…However, this reduction in apoC-III is probably not a direct effect on apoC-III synthesis because the total plasma apoC-III was not reduced. It appears that the apoC-III was simply transferred to HDL, probably because of an increase in LPL activity, as previously described for both of these therapies [5][6][7][8]. Consistent with this interpretation, the apoC-III/apoB ratio in VLDL, which represents the number of apoC-III molecules per particle, was not reduced by therapy.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, this reduction in apoC-III is probably not a direct effect on apoC-III synthesis because the total plasma apoC-III was not reduced. It appears that the apoC-III was simply transferred to HDL, probably because of an increase in LPL activity, as previously described for both of these therapies [5][6][7][8]. Consistent with this interpretation, the apoC-III/apoB ratio in VLDL, which represents the number of apoC-III molecules per particle, was not reduced by therapy.…”
Section: Discussionsupporting
confidence: 81%
“…The ABCA1 transporter activity, which is responsible for cholesterol efflux from most tissues, including vascular foam cells, has been shown to be stimulated by both cAMP [1,2] and PPARc [3,4]. Similarly, LPL is also stimulated by both cAMP [5,6] and PPARc [7,8]. Laplante et al [8] demonstrated that PPARc activated LPL only in subcutaneous fat, not visceral fat.…”
Section: Introductionmentioning
confidence: 94%
“…Lipase hastens the liberation of free fatty acid from triglyceride which acts both as fuel for thermogenesis and as an activator of UCP1 (Kuusela et al, 1997). Apart from cold exposure, nonshivering thermogenesis can also be induced by using β3-AR agonists such as BRL-35135 and CL-316243 (Klaus et al, 2001;Shih and Taberner, 1995).…”
Section: Activation Of Brown Fat Mediated Thermogenesismentioning
confidence: 98%
“…For regulation of the expression of the uncoupling protein UCP1 (53,54) and lipoprotein lipase (55), an ␣ 1 -adrenergic component has been identified, and a synergistic interaction between ␣ 1 -and ␤-receptors and signaling pathways has been demonstrated for both thyroxine deiodinase (40) and c-fos (22) expression. Here, unexpectedly, we demonstrate that even for a process that has been accepted to be essentially ␤-adrenergically stimulated and cAMP-mediated, a strong ␣ 1 /␤-receptor synergism can be observed.…”
Section: Discussionmentioning
confidence: 99%